2018
DOI: 10.3126/bjhs.v3i1.19756
|View full text |Cite
|
Sign up to set email alerts
|

Study of Protein/creatinine Ratio in Preeclampsia as an Alternative to 24 Hours Urine Protein in Manipal Teaching Hospital of Nepal

Abstract: Introduction: Hypertensive disorder in pregnancy complicates around 5 to 10% of all pregnancies. It is one of the leading causes of maternal and fetal morbidity and mortality. Measurement of protein excretion by 24 -hour urine protein collection is gold standard but as it is time consuming, an alternative method like random urine protein/creatinine ratio is required.Objectives: The aim of this study was to assess the diagnostic accuracy of urine protein/ creatinine ratio compared with 24-hour urine protein as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In a similar study involving Indian pregnant women, Shrestha et al 11 (2018) reported a similar positive predictive value of 97.2% for spot urinary protein to creatinine ratio in the diagnosis of preeclampsia. Similar results have also been reported by Bhadarka et al 31 (2018) and Shreya et al 32 (2015) in other Indian studies who observed the PPV of spot urinary protein to creatinine ratio to be 95.0% and 94.0% respectively.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…In a similar study involving Indian pregnant women, Shrestha et al 11 (2018) reported a similar positive predictive value of 97.2% for spot urinary protein to creatinine ratio in the diagnosis of preeclampsia. Similar results have also been reported by Bhadarka et al 31 (2018) and Shreya et al 32 (2015) in other Indian studies who observed the PPV of spot urinary protein to creatinine ratio to be 95.0% and 94.0% respectively.…”
Section: Discussionmentioning
confidence: 82%
“…2 Recent studies claimed that urinary protein to creatinine ratio in a spot urine specimen was equally reliable in the diagnosis of preeclampsia but it was relatively quicker in sample collection and reporting and could improve the outcome by saving valuable time. [9][10][11][12] However, there was a controversy in the existing literature [9][10][11][12][13] regarding the positive predictive value of spot urinary protein to creatinine ratio, which caused the present study. The aim of this study was to determine the positive predictive value of spot urinary protein to creatinine ratio for the diagnosis of pre-eclampsia, taking 24-hour urinary protein as the gold standard.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation